A expansão do setor sucroenergético no estado de São Paulo - Lopes, Mateus Francisco [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The changes occurring in Brazilian agriculture, with the inclusion of agro-industrial activities in your mode of production, must be analyzed to verify the changes in the behavior of territorial dynamics. Through changing the Rural Complex, traditional for the Agroindustrial Complex tightly integrated with trade and industry brought many consequences for the rural population, with regard to employment. Understanding this transformation capitalist the field is needed to analyze the actors involved in this process and the policies adopted for the expansion of sugar and ethanol activity in the State of São Paulo and the consequences for the spatial organization. The expansion of cane production areas were governed by the Institute of Sugar and Alcohol (IAA), the National Alcohol Program (PROÁLCOOL) Development Plan for the West of São Paulo - PRO-WEST and Expansion Program for the production of Canavicultura for production of fuel for the State of São Paulo (PROCANA). The occupation of these agroindustrial facilities in rural spaces contextualized by territorialization of the rural complex, in that sense, understanding these concepts is a key part development in the research. therefore, are concepts of fundamental importance to geographical science, and interpreting their function and construction in rural spaces

As transformações ocorridas na agricultura brasileira, com a inserção das atividades agroindustriais no seu modo de produzir, devem ser analisadas para verificar as mudanças no comportamento da dinâmica territorial. Com isso, a alteração do Complexo Rural, tradicional, para o Complexo Agroindustrial altamente integrado com o comércio e indústria provocaram inúmeras conseqüências para a população rural, no que se refere às relações de trabalho. O entendimento dessa transformação capitalista no campo é necessário para analisar os atores envolvidos nesse processo e as políticas adotadas para a expansão da atividade sucroalcooleira no Estado de São Paulo e as conseqüências para a organização espacial. A expansão das áreas de produção canavieira foram regidas pelo Instituto do Açúcar e do Álcool (IAA), Programa Nacional do Álcool (PROÁLCOOL), Plano de Desenvolvimento do Oeste do Estado de São Paulo – PRÓ-OESTE e o Programa de Expansão da Canavicultura para produção de Combustível do Estado de São Paulo (PROCANA). A ocupação dessas instalações agroindustriais no espaço rural contextualizou-se por meio da territorialização do Complexo Rural, nesse sentido, compreender esses conceitos é peça-chave no desenvolvimento da pesquisa. Pois, são conceitos de fundamental importância para a Ciência Geográfica, e interpretando a sua função e construção no espaço rural
Keywords: Agroindustria canavieira - Política governamental; Agroindústria; Cana-de-açúcar; Geografia agrícola; Espaço agricola; Sugarcane industry - Government policy; Sugarcane; Agricultural geography